Mitochondrial Dysfunction in Down Syndrome: From Pathology to Therapy. (10th February 2023) - Tan, Kai-Leng; Lee, Han-Chung; Cheah, Pike-See; Ling, King-Hwa
Highlights: Mitochondrial dysfunctions in Down syndrome are characterised by changes in the morphology, function, biogenesis and dynamics and gene expression/networks. Dysfunctional mitochondrial affects OXPHOS machinery in energy production in Down syndrome. HSA21 gene dosage or global disruption of gene networks leads to mitochondrial dysfunction. Mitochondria-targeted therapeutic agents can alleviate mitochondrial dysfunctions in the Down syndrome brain. Abstract: Mitochondrial dysfunctions have been described in Down syndrome (DS) caused by either partial or full trisomy of chromosome 21 (HSA21). Mitochondria play a crucial role in various vital functions in eukaryotic cells, especially in energy production, calcium homeostasis and programmed cell death. The function of mitochondria is primarily regulated by genes encoded in the mitochondrion and nucleus. Many genes on HSA21 are involved in oxidative phosphorylation (OXPHOS) and regulation of mitochondrial functions. This review highlights the HSA21 dosage-sensitive nuclear-encoded mitochondrial genes associated with overexpression-related phenotypes seen in DS. This includes impaired mitochondrial dynamics, structural defects and dysregulated bioenergetic profiles such as OXPHOS deficiency and reduced ATP production. Various therapeutic approaches for modulating energy deficits in DS, effects and molecular mechanism of gene therapy and drugs that exert protective effects through modulation of mitochondrial function and attenuation of oxidative stress in DS cells were discussed. It is prudent that improving DS pathophysiological conditions or quality of life may be feasible by targeting something as simple as cellular mitochondrial biogenesis and function.